Communicative intentions in autism spectrum disorder. (November 2020) - Schütz, Magdalena; Ciaramidaro, Angela; Martinelli, Anne; Öller, Ramona; Hartmann, Daniela; Hein, Grit; Iotzov, Vassil; Colle, Livia; Becchio, Cristina; Walter, Henrik; Freitag, Christine M.
Highlights: ASD show reduced activation in the human middle temporal complex (hMT+). Decreased PMC activation reflects reduced preparedness for social interaction in ASD. No global MNS or MZS deficit can be found for ASD. Abstract: Background: Deficits in social communication and interaction are among the core symptoms of Autism Spectrum Disorder (ASD). Intention understanding in particular has been shown to be impaired in ASD. However, only one previous study has explicitly assessed the understanding of communicative intentions in ASD. Thus, the aim of the present study was to compare neural activation during the observation of communicative and non-communicative actions in participants with ASD and typically developing (TD) controls using functional magnetic resonance imaging (fMRI). Based on recent findings that show that the degree of involvement of the observer has an impact on neural activation, the present study included first- and third-person perspective stimuli. Method: Twenty-five male TD (mean age 20.41 ± 3.39) and twenty-two male participants with ASD (mean age 18.60 ± 3.55) were included. Stimuli consisted of videos in which actors performed an action with an everyday object. Actions were either private or communicative; communicative actions were either directed at the observer (first-person) or at a third person. Results: The ASD group showed reduced activation in the human middle temporal complex (hMT+) across all conditions. However, modulation of activation in response to different conditions remained intact in ASD. Additionally, while TD showed an increase in premotor cortex (PMC) activation in response to communicative actions directed at them, the ASD group showed a decrease in activation. Conclusions: These findings suggest an early processing deficit with regard to human biological motion in ASD. Furthermore, results reflect a reduced preparedness for social interactions in ASD compared to TD when addressed directly.